Figure 5 from: Sikes D, Stockbridge J (2013) Description of Caurinus tlagu, new species, from Prince of Wales Island, Alaska (Mecoptera, Boreidae, Caurininae). ZooKeys 316: 35-53. https://doi.org/10.3897/zookeys.316.5400 - Sikes, Derek; Stockbridge, Jill (Zenodo, 2013)
Figure 5 - A ventral view of female Caurinus tlagu (UAM:Ento:203239) showing 8th sternum with shallow median emargination / notch, scale bar = 500 µm B ventral view of abdomen of female Caurinus dectes (UAM:Ento:228458) showing 8th sternum with a pronounced notch, scale bar = 200 µm C ventral view of abdomen of female Caurinus tlagu (UAM:Ento:203011) showing 8th sternum with shallow emargination / notch, scale bar = 200 µm.